2010
DOI: 10.1177/000313481007601237
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Right Subclavian Artery–Esophageal Fistula

Abstract: Letters to the Editor should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 3 double-spaced pages excluding an Abstract and sub-headings with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…2 Prolonged endotracheal and/or nasogastric intubation is the most common predisposing factor for fistula formation. On literature review, we found a total of 17 cases of aberrant subclavian artery–esophageal fistula in which the prolonged endotracheal and/or nasogastric intubation has been listed as a causative factor of fistula formation 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ( Table 1 ). The average duration between NGT and endotracheal tube (ET) placement and first episode of bleeding is of 29 (6–56) and 23 (13–31) days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prolonged endotracheal and/or nasogastric intubation is the most common predisposing factor for fistula formation. On literature review, we found a total of 17 cases of aberrant subclavian artery–esophageal fistula in which the prolonged endotracheal and/or nasogastric intubation has been listed as a causative factor of fistula formation 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ( Table 1 ). The average duration between NGT and endotracheal tube (ET) placement and first episode of bleeding is of 29 (6–56) and 23 (13–31) days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the prolonged use of NG and/or ET tubes in a patient with a retroesophageal aberrant artery or other aortic arch anomalies forming a vascular ring may make the patient susceptible to arterial-esophageal fistula formation. A literature search showed a total of 40 documented cases of aberrant subclavian artery and esophageal fistulae ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Among those cases, a long-term use of NG and/or ET tube was thought to be the main cause of fistula formation in at least 18 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The most common etiology for development of ARSA-esophageal fistula appeared to be secondary to compression, friction, or pressure necrosis from recent instrumentation with an endotracheal tube, nasogastric tube, or tracheostomy tube, seen in 14 of the 33 summarized cases. 14,15,17,19,21,22,24,27,29,31,[38][39][40][41] Fistula development from prior placement of esophageal stent was noted in 5 cases. 34,36,42,43 Other reported causes for fistula formation included placement of a salivary bypass tube and a possible consequence of gastric pull-up surgery.…”
Section: Discussionmentioning
confidence: 99%
“…44 Reported cases in adults involved treatment with surgery alone in 5 cases, 11,16,26,30,38 endovascular repair alone in 2 cases, 41,42 and a combination of endovascular and surgical intervention in 6 cases. 28,29,31,35,36,43 Balloon tamponade was performed in 16 cases, 1,14,15,21,22,24,25,27-29,31-33,35-37 with 3 of those 16 performed solely with endovascular repair. 1,27,32 Six of the 11 patients who underwent either surgery alone or surgery with endovascular repair survived (55%), 28,30,31,36,38,43 whereas only 1 of the 5 cases of endovascular repair with or without balloon tamponade survived (20%).…”
Section: Discussionmentioning
confidence: 99%